The Leadership in Action Series : On Leading the Global Organization. - Rush, Stephen; Hannum, Kelly M. (La Vergne : Center for Creative Leadership, 2013)
Organizations that have operations around the globe have become the norm rather than the exception. This means they need leaders with the requisite skills-including international business knowledge, cultural adaptability, perspective taking, and innovation-to respond effectively to the challenges and complexity of global leadership. This collection of seventeen pieces-written by the Center for Creative Leadership's highly experienced and knowledgeable faculty members and researchers as well as by prominent practitioners and scholars in the fields of leadership and leadership development-explores the important topic of leading the global organization from a number of angles. What can organizations and leaders do to develop the skills needed to excel in a global context? How can global leaders manage the relationship between corporate headquarters and local offices? How can organizations best handle the challenge of boundary-spanning leadership? Readers will come away with newly found knowledge on these and other questions and newly formed thoughts on how they can successfully meet the demands of leading the global organization.
Front cover -- Half title page -- About CCL -- Full title page -- Copyright page -- CONTENTS -- IN BRIEF -- INTRODUCTION -- Part I: BECOMING A GLOBAL LEADER -- Global Managing: Mastering the Spin of a Complex World -- Challenge Match: The Stakes Grow Higher for Global Leaders -- For Global Managers, a World of Difference -- Leading Globally Requires a Fundamental Shift -- Adult Development Theory May Boost Global Leadership -- Global Leaders Face Challenges in Asia -- Getting to the Source: Four Perspectives on Leadership -- Hatching a Plan: Developing Leadership Talent in Emerging Markets -- Across the Boards: How Chairmen's Roles Differ Around the World -- Part II: WHY CULTURAL ADAPTABILITY IS IMPORTANT -- Bridging Boundaries: Meeting the Challenge of Workplace Diversity -- Cultural Intelligence and the Global Economy -- Cultural Adaptability: It's About More Than Using the Right Fork -- One Prescription for Working Across Cultures -- Getting the Message: How to Feel Your Way with Other Cultures -- Gaining a Critical Edge in Mastering Globalization -- If It's Lagom, This Must Be Sweden -- Seeking a Model for Leadership Development in China -- ABOUT THE CONTRIBUTORS -- FURTHER READING -- Ordering Information -- Back cover.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: International business enterprises -- Management; Leadership -- Cross-cultural studies; Management -- Cross-cultural studies; Electronic books